A new ERA? The changing face of journalism research in Australia. Issue 1 (1st June 2020) - Wake, Alexandra; Martin, Fiona R.; Backhaus, Bridget
In 2011, Michael Bromley and Regan Neal's survey of Australian journalism academics revealed low levels of critical research participation and productivity, and the under-realized potential of younger, female journalism academics. Nearly a decade on, our 2019 snapshot study, inspired by Bromley and Neal, explores the current state of journalism research and education in Australian universities. It examines the changing profile of journalism staff, their publishing productivity and the evaluation and funding of their research, as well as attitudes towards non-traditional research outputs (NTROs) and engagement and impact assessment. Our study indicates that early- and mid-career journalism researchers in Australia, particularly women, continue to need research training, mentoring and support in securing competitive external grants, as well as encouragement to collaborate and benchmark their research internationally. There is also a new imperative to help researchers and their institutions recognize excellence and diversity in journalism NTROs and to understand measures of engagement and impact. Finally, we flag the importance of monitoring changes to the classification of journalism research following the Australian and New Zealand Standard Research Classification review of field of research codes.